2019
DOI: 10.3390/f10070567
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi Effectively Enhances the Growth of Gleditsia sinensis Lam. Seedlings under Greenhouse Conditions

Abstract: The Chinese honey locust tree Gleditsia sinensis Lam. (Fabaceae) is a precious ecological and economic tree species that has wide-ranging usage. However, knowledge regarding seedling cultivation (especially the use of arbuscular mycorrhizal fungi (AMF)) is scarce, which limits the developent of Gleditsia plantations. A pot experiment was carried out under greenhouse conditions to estimate the effects of three AMF strains (Funneliformis mosseae 1, Funneliformis mosseae 2, and Diversispora tortuosa) on the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
5
14
0
Order By: Relevance
“…Despite the variability response of crops to the mycorrhizae application (Estaún, Calvet, & Camprubí, 2010;Kokkoris, Hamel, & Hart, 2019;Saia et al, 2020), our result is in line with number of studies related with significant contribution of mycorrhizae in increasing the crops yield (Bhardwaj, Ansari, Sahoo, & Tuteja, 2014;Saleh, Anshary, & Made, 2018;Samanhudi, Yunus, Pujiasmanto, Cahyani, & Lestariana, 2017;Wang et al, 2019). This study also confirmed the importance of AM application on the allium species that have limited expansion of the root system as one obstacle to absorb sufficient nutrients for plant growth (Golubkina et al, 2020).…”
Section: Effect Of Mycorrhizae On Shallot Roots and Yieldssupporting
confidence: 91%
“…Despite the variability response of crops to the mycorrhizae application (Estaún, Calvet, & Camprubí, 2010;Kokkoris, Hamel, & Hart, 2019;Saia et al, 2020), our result is in line with number of studies related with significant contribution of mycorrhizae in increasing the crops yield (Bhardwaj, Ansari, Sahoo, & Tuteja, 2014;Saleh, Anshary, & Made, 2018;Samanhudi, Yunus, Pujiasmanto, Cahyani, & Lestariana, 2017;Wang et al, 2019). This study also confirmed the importance of AM application on the allium species that have limited expansion of the root system as one obstacle to absorb sufficient nutrients for plant growth (Golubkina et al, 2020).…”
Section: Effect Of Mycorrhizae On Shallot Roots and Yieldssupporting
confidence: 91%
“…Each plant was inoculated with one hundred AMF spores, and 20 mL of actinobacterial inoculum was added to the substrate near the root zone for each seedling. The experiment was performed with a schedule of regular watering and feeding using the modified Hoagland's nutrient solution [40] once a week. Values of plant height, leaf number, stem diameter, and branch number were recorded at 15, 30, 45, 60, 100, and 180 days after planting.…”
Section: Experimental Designmentioning
confidence: 99%
“…AMF inoculation since seedling in forest plants (Gleditsia sinensis Lam) was also reported to increase seedling height, stem diameter, dry weight of seed biomass, chlorophyll content, photosynthetic rate, and NPK content in root, stem, and leaf tissue [13]. Likewise, inoculation of AMF in nurseries on tropical plant seeds was also reported to increase plant height, root diameter, and biomass [16] as well as N and P content of seedlings and root dry weight in forest plant seedlings [17].…”
Section: Easy To Applymentioning
confidence: 97%
“…Likewise, mycorrhizae play a role in accelerating the growth or emergence of secondary roots in sugarcane seedling [12]. Mycorrhizae also appeared to have a significant role in increasing the growth of forest plant seedlings in the nursery, the increase in leaf chlorophyll content, photosynthesis rate, NPK content in root, stem and leaf compared to plants without mycorrhizal inoculation [13].…”
Section: Introductionmentioning
confidence: 96%